2001
DOI: 10.1139/x00-167
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and nitrogen release from decomposing woody roots in coniferous forests of the Pacific Northwest: a chronosequence approach

Abstract: Decomposition of woody roots in Sitka spruce (Picea sitchensis (Bong.) Carrière), Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco), and ponderosa pine (Pinus ponderosa P. Laws. ex C. Laws.) dominated forests in Oregon, U.S.A. was studied using a chronosequence. Roots of five coniferous species were excavated from stumps with ages up to 46 years old. In order of increasing decomposition rate constant (k) the species were Douglas-fir < Sitka spruce < lodgepole pine (Pinus contorta Dougl. ex Loud.) < w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 29 publications
1
32
3
Order By: Relevance
“…Finally, in longer term from ecological perspective, the decay roots may turn into organic substance, contributing to plant nutrients and improving soil fertility for sustainable growth of tree. This would help maintain the nutrient cycle in soil and ecology (Ostertag and Hobbie, 1999;Chen et al, 2001). In the future, the observed changes in ks or infiltration rate due to different plant spacing can be verified using in-situ double-ring 25 infiltration tests (such as those conducted by Leung et al (2015a)), which might give a better indication than tests on small laboratory samples obtained from cores.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in longer term from ecological perspective, the decay roots may turn into organic substance, contributing to plant nutrients and improving soil fertility for sustainable growth of tree. This would help maintain the nutrient cycle in soil and ecology (Ostertag and Hobbie, 1999;Chen et al, 2001). In the future, the observed changes in ks or infiltration rate due to different plant spacing can be verified using in-situ double-ring 25 infiltration tests (such as those conducted by Leung et al (2015a)), which might give a better indication than tests on small laboratory samples obtained from cores.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that initial tissue chemistry explained the greatest proportion of variance in decomposition rate (85%), while environmental variables, most notably temperature, precipitation and actual evapotranspiration (AET) played a secondary role. Since Silver and Miya's analysis, fine root decomposition studies have largely focused on the effects of litter quality on rate of decay and generally support the notion that litter quality regulates microbial activity and thus decomposition (Chen et al 2001;Lemma et al 2007). In general, decay rates of fine roots are positively correlated with initial concentrations of Ca, Mg, Mn, N and P and negatively correlated with C:N, lignin:N, cellulose, and phenolic compounds including tannins, and lignin (Berg et al 1998;John et al 2002;Jalota et al 2006;Wang et al 2010;Tong et al 2012;García-Palacios et al 2016;Guerrero-Ramírez et al 2016;Roumet et al 2016).…”
Section: Factors That Influence Fine Root Decompositionmentioning
confidence: 95%
“…Root decomposition is closely related to root turnover, which has been shown to be highly variable depending on tree species and also on sitespecific and climatic conditions (Finer et al, 2011;Brunner et al, 2012). We assessed this uncertainty by calculating the root decay for different decomposition rates as given by Ngao et al (2007) and Chen et al (2001). The calculated fine-root mass loss was 25 % of the initial mass for the first year after trenching.…”
Section: Approach 2: On the Indirect Quantification Of The Neementioning
confidence: 99%